Can tenants afford to care? Investigating the willingness-to-pay for improved energy efficiency of rental tenants and returns to investment for landlords - Matthew Collins; John A. Curtis (The Economic and Social Research Institute (ESRI), 2017)
Throughout the developed world, residential buildings in the rental sector exhibit lower levels of energy efficiency than the owner-occupied building stock. A double-bounded dichotomous choice contingent valuation method is used to examine how much renters are willing to pay in their monthly rent for improved energy efficiency, measured via energy performance certificates. The results of this analysis are used to examine the returns to investment available to landlords for various measures. Using an administrative dataset of residential retrofits, we examine the upfront cost to landlords of engaging in energy efficiency retrofits of varying depths and calculate the relevant payback period. Conditional upon possessing a non-zero willingness-to-pay, we find that tenants in Ireland are willing to pay an average of over exteuro40 for each one-grade improvement in their accommodation's Building Energy Rating. We find short payback periods for attic and cavity wall insulation and prohibitively long payback periods for external wall insulation and solar heating.
Keywords: 330